HUBUNGAN SANITASI DENGAN INFEKSI TELUR CACING PADA ANAK SEKOLAH DASAR - Sri Ida Yani (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2021)
Worm infections in humans are caused by intestinal nematode worms, namely Soil Transmitted Helminths (STH), which are transmitted through contaminated soil through direct contact with parasite eggs or larvae in the soil. School-age children are a group that has a high risk of STH infection because they are often exposed to soil, contaminated water, and lack of awareness of personal hygiene. Soil Transmitted Helminth (STH) transmission through eggs is excreted in the form of feces or urine which contaminates soil and water that has poor sanitation and water supply. Worm infection in children of basic age can cause stunted growth and development of children, disability, and blindness. The purpose of this study was to determine the relationship between environmental sanitation and infection of intestinal worm eggs (Soil Transmitted Helmint) in elementary school children in Bangli Regency. Respondents who were examined were 30, namely elementary school students in Bangli Regency starting from grades 1-6. School environmental sanitation data obtained by a questionnaire with the observation method. The data on worms for the respondents were obtained by taking fecal samples and examined using the direct method at the Parasitology Laboratory of STIKes Wira Medika Bali. The results showed that the overall sanitation condition of the school environment in Bangli Regency was 90% good and the prevalence of worm infections in elementary school children in Bangli Regency was 3.3%. There is no relationship between environmental sanitation and infection of intestinal worm eggs (Soil Transmitted Helmint) in elementary school children in Bangli Regency (p-value 0.05).. Keywords: Soil Transmitted Helmints, elementary school children, direct slide method, Necator americanus